Knowledge and attitudes influence in implementation of household waste management program - Yemima Marnalita Hasibuan; Filson Maratur Sidjabat (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2020)
Waste is one of the big problems often faced by metropolitan cities like DKI Jakarta. The Environmental Agency of DKI Jakarta's research stated that DKI Jakarta produces 7500 tons of waste per day with 60.5% coming from residential. Therefore, the DKI Jakarta government initiated the "Sampah Tanggung Jawab Bersama" (SAMTAMA) to mobilize residential people to manage waste from its source at certain locations as a pilot, one of the locations is RT 10/RW 03 Cempaka Putih Timur. This location is regarded optimal in implementing the SAMTAMA program. Based on this, study aim was to find out whether knowledge and attitude affect the implementation SAMTAMA program. The method implemented in measuring the behavior using a questionnaire with Likert Scale. Multiple linear regression was applied. Knowledge and attitudes influenced the implementation SAMTAMA program behavior.